Analysis of Al-Qur'an Memorization Ability based on STIFIn Intuiting and Feeling Test Results on Tahfidz Program Students of MTs Unggulan Nuris Jember - Salafiyah, Binti Risalatus; Sahlan, Moh.; Wahyuni, Indah (CV. Media Digital Publikasi Indonesia, 2025)
Memorizing the Qur'an is a highly valued activity in Islam, but this process is not always easy and can be affected by various factors, both internal and external. The STIFIn test, which is a tool for mapping individual potential based on basic brain functions, was used to identify students' learning styles that can support the memorization process. This research uses a descriptive qualitative approach with a case study method, which involves collecting data through observation, interviews, and documentation in the field. The data analysis used in the research is interactive analysis, namely through data collection, data presentation and conclusion drawing. The results show that students with intuiting intelligence type rely more on semantic memory and imagination to understand the context and translation, they start the memorization process by reading and understanding the translation which serves as a memory booster, while feeling type students emphasize more on a conducive learning atmosphere and meticulous repetition where they prefer to memorize gradually with a focus on deep understanding of each lafaz and its meaning. These findings provide important insights into effective strategies in memorizing the Qur'an, as well as the importance of understanding each student's potential to improve learning effectiveness.